Penerapan Multimedia Interaktif Game Edukasi Matematika untuk Siswa Sekolah Dasar Menggunakan Metode Research and Development - Rafi Augie Ramadhan; Nono Heryana; Adhi Rizal (Peneliti.net, 2021)
Games have become a means of entertainment that are most in demand by people from the young to the old. An example of the technology used at this time is Multimedia Game Education. This technology offers a fun and efficient learning experience, by displaying 2D and 3D image objects. This study aims to introduce the material about Mathematics in the second grade elementary school subjects by incorporating Interactive Educational Games in the learning system at SD Abdi Negara 2 Cibarusah. The educational side of this game is in the form of fun counting lessons and there are material questions to learn for second graders. The research methods used in this study include the Research and Development method, namely by using preliminary study techniques or exploratory studies to examine, investigate, and collect information by collecting data through observation and interviews. The result of this research is the implementation of making an Android-based educational game application: